“Cameralism” or “patrimonialism”: at the origins of Peter the Great’s reformation of higher management in Russia - N. A. Omelchenko (Вестник университета)
The article presents the author’s interpretation of Petrine reforms of higher management in Russia. The author of the article asks the question, how successful was the attempt made by Peter I to create a rational system of public administration in Russia according to Western models? Among the main features of Peter’s reformation, the author highlights the lack of a clear and well-thought-out plan for the reforms carried out by Peter I, most of which were mainly “experimental” in nature, were carried out hastily and were subordinated to the tasks of the ongoing war with Sweden. Based on the analysis of the transformations carried out at the beginning of the XVIII century in the system of higher administration, the author of the article concludes about the strengthening of the personal principle in public administration during the reign of Peter I, which casts doubt on the widespread opinion about the formation of a rational system of public administration during the reforms carried out by Peter I. According to the author of the article, the use of Weber’s concept of “patrimonialism” (“patrimonial bureaucracy”) as a special type of domination based on the principle of personal loyalty to the patrimonial ruler (monarch) may become more correct in this regard when describing the Peter’s administrative system.